IDENTIFICATION OF MEATS USING RANDOM AMPLIFIED POLYMORPHIC DNA (RAPD) TECHNIQUE - Arslan, Ali; İlhak, İrfan; Calicioglu, Mehmet; Karahan, Murat (My University, 2005)
Use of a simpler, faster and reliable method for identification of species of origin in fresh and processed meat products is required to prevent unethical practices that may occur in the meat industry. The effectiveness of a random amplified polymorphic DNA (RAPD) method for identification of fresh meats from cattle, goat, sheep, camel, pork, wild swine, donkey, cat, dog, rabbit or bear origin was evaluated using a 10-base primer (ACGACCCACG). The method was also used to determine the species in a 1 : 1 mix of raw minced meat from sheep-pork, horse-beef or beef-sheep. Characteristic RAPD profiles for each species were obtained. However, efficacy of the technique in identifying species in meat mixtures varied depending on the species in the mix. These results indicate that RAPD may be useful for identification of meat samples from single species, such as intact meat samples, whereas caution should be exercised in identification of origin of species in minced meat that may consist of multiple species.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: RAPD PCR Meat identification